Cognitive outcomes after focused ultrasound thalamotomy for tremor: Results from the COGNIFUS (COGNitive in Focused UltraSound) study. (January 2023) - Saporito, Gennaro; Sucapane, Patrizia; Ornello, Raffaele; Cerone, Davide; Bruno, Federico; Splendiani, Alessandra; Masciocchi, Carlo; Ricci, Alessandro; Marini, Carmine; Sacco, Simona; Pistoia, Francesca
Abstract: Introduction: Magnetic resonance-guided focused ultrasound (MRgFUS) thalamotomy is an innovative method for the unilateral treatment of essential tremor (ET) and Parkinson's disease (PD) related tremor. Our aim was to assess cognitive changes following MRgFUS thalamotomy to better investigate its safety profile. Methods: We prospectively investigated the cognitive and neurobehavioral profile of patients consecutively undergoing MRgFUS within a 2-year period. Patients had a comprehensive clinical and neuropsychological assessment before and six months after MRgFUS thalamotomy. Results: The final sample consisted of 40 patients (males 38; mean age±SD 67.7 ± 10.7; mean disease duration±SD 9.3 ± 5.6; ET 22, PD 18 patients). For the whole sample, improvements were detected in tremor (Fahn-Tolosa-Marin Clinical Rating Scale for tremor 35.79 ± 14.39 vs 23.03 ± 10.95; p < 0.001), anxiety feelings (Hamilton Anxiety rating scale 5.36 ± 3.80 vs 2.54 ± 3.28, p < 0.001), in the overall cognitive status (MMSE 25.93 ± 3.76 vs 27.54 ± 2.46, p 0.003; MOCA 22.80 ± 4.08 vs 24.48 ± 3.13, p < 0.001), and in quality of life (Quality of life in Essential Tremor Questionnaire 36.14 ± 12.91 vs 5.14 ± 6.90, p < 0.001 and PD Questionnaire-8 5.61 ± 4.65 vs 1.39 ± 2.33, p 0.001). No changes were detected in frontal and executive functions, verbal fluency and memory, abstract reasoning and problem-solving abilities. Conclusion: Our study moves a step forward in establishing the cognitive sequelae of MRgFUS thalamotomy and in endorsing effectiveness and safety. Highlights: Unilateral MRgFUS thalamotomy is an innovative treatment for tremor. Staged bilateral MRgFUS is under investigation and is gradually taking hold. Delayed cognitive consequences of unilateral MRgFUS thalamotomy are controversial. Our study suggests the absence of cognitive changes after unilateral treatment. This endorses the safety profile of MRgFUS thalamotomy.